The Performance of Multi-Factor Term Structure Models for Pricing and Hedging Caps and Swaptions - Driessen, Joost; Klaassen, Pieter; Melenberg, Bertrand (Journal of Financial and Quantitative Analysis, 2003)
Joost Driessen, Pieter Klaassen, Bertrand Melenberg, The Performance of Multi-Factor Term Structure Models for Pricing and Hedging Caps and Swaptions, The Journal of Financial and Quantitative Analysis, Vol. 38, No. 3 (Sep., 2003), pp. 635-672